International Conference on Wireless, Intelligent, and Distributed Environment for Communication WIDECOM 2018 (Lecture Notes on Data Engineering and Communications Technologies,, 2018)
This book presents the proceedings of the International Conference on Wireless Intelligent and Distributed Environment for Communication (WIDECOM 2018), organized by SRM University, NCR Campus, New Delhi, India, February 16-18, 2018. The conference focuses on challenges with respect to the dependability of integrated applications and intelligence-driven security threats against the platforms supporting these applications. The WIDECOM 2018 proceedings features papers addressing issues related to the new dependability paradigms, design, control, and management of next generation networks, performance of dependable network computing and mobile systems, protocols that deal with network computing, mobile/ubiquitous systems, cloud systems, and Internet of Things (IoT) systems. The proceeding is a valuable reference for researchers, instructors, students, scientists, engineers, managers, and industry practitioners, in industry, in the aforementioned areas. The book's structure and content is organized in such a manner that makes it useful at a variety of learning levels. Presents the proceedings of the International Conference on Wireless Intelligent and Distributed Environment for Communication (WIDECOM 2018), organized by SRM University, NCR Campus, New Delhi, India, February 16-18, 2018; Includes an array of topics related to new dependability paradigms, design, control, and management of next generation networks, performance of dependable network computing and mobile systems, protocols that deal with network computing, mobile/ubiquitous systems, cloud systems, and Internet of Things (IoT) systems; Addresses issues related to the design and performance of dependable network computing and systems and to the security of these systems. .